Testing the link between mergers and AGN in the Arp 245 system. Issue Volume 15:Issue S359(2020) (March 2019) - Lösch, Elismar; Ruschel-Dutra, Daniel
Abstract: Galaxy mergers are known to drive an inflow of gas towards galactic centers, potentia- lly leading to both star formation and nuclear activity. In this work we aim to study how a major merger event in the ARP 245 system is linked with the triggering of an active galactic nucleus (AGN) in the NGC galaxy 2992. We employed three galaxy collision numerical simulations and calculated the inflow of gas through four different concentric spherical surfaces around the galactic centers, estimating an upper limit for the luminosity of an AGN being fed the amount of gas crossing the innermost spherical surface. We found that these simulations predict reasonable gas inflow rates when compared with the observed AGN luminosity in NGC 2992.